2020
DOI: 10.1101/2020.05.09.085969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fungi are colder than their surroundings

Abstract: Fungi play essential roles in global ecology and economy, but their thermal biology is widely unknown. Infrared imaging revealed that mushrooms, yeasts, and molds each maintained colder temperatures than their surroundings. Fungal specimens are to be ~2.5 °C colder than the surrounding temperature. Time-lapse infrared images of Pleurotus ostreatus revealed hypothermia throughout mushroom growth and after detachment from mycelium. The hymenium was coldest, and different areas of the mushroom exhibit distinct th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…These results showed that the active fungi mycelium is approximately 1.1 to 2.1 °C cooler than the non-active mycelium and the non-colonized PDA surface area (in this case the surface of the control plates). Similar conclusions are reported by Cordero et al [30], who reported that the temperature difference between the fungus and its surroundings ranged from 0.5 to 5.0 °C, depending on the fungal specimens. The active mycelium maintains colder temperatures than its surroundings as well as than the non-active mycelium via evapotranspiration, which can be measured by collecting the condensed water droplets above molt biofilms.…”
Section: Fungal Mycelium Trgb Imaging In Vitrosupporting
confidence: 90%
See 1 more Smart Citation
“…These results showed that the active fungi mycelium is approximately 1.1 to 2.1 °C cooler than the non-active mycelium and the non-colonized PDA surface area (in this case the surface of the control plates). Similar conclusions are reported by Cordero et al [30], who reported that the temperature difference between the fungus and its surroundings ranged from 0.5 to 5.0 °C, depending on the fungal specimens. The active mycelium maintains colder temperatures than its surroundings as well as than the non-active mycelium via evapotranspiration, which can be measured by collecting the condensed water droplets above molt biofilms.…”
Section: Fungal Mycelium Trgb Imaging In Vitrosupporting
confidence: 90%
“…It has been shown that thermal imaging techniques were able to visualize infections of Cercospora beticola at an early stage on sugar beet leaves, before damage appeared [28,29]. In addition, infrared imaging revealed that mushrooms, yeasts, and molds each maintained lower temperatures than their surroundings [30]. Spot temperature changes on leaves surface may therefore indicate signs of possible infection.…”
Section: Introductionmentioning
confidence: 99%